The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1515/zna-1991-0711
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of Diphenyl Polyenes

Abstract: We describe an unusual temperature dependence of l,8-diphenyl-l,3,5,7-octatetraene absorption in polyvinyl alcohol) films. Upon heating above 80 °C, the optical density (in the long wavelength region) of this compound increases rapidly. A sample heated to 150 °C has a nearly twenty times higher optical density than a non-heated sample. This effect is not reversible: Once the sample is heated it retains its absorbance on cooling to room temperature. In our opinion, the effect has its origin in changes of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…The method of preparing PDPB samples in PVA and the measurements of absorption spectra at differ ent temperatures were reported in [1]. PDPB was from Dr. D. Gloyna (Humboldt-Universität zu Berlin), poly (vinyl alcohol) (PVA, 100% hydrolyzed, molecular weight 106,000-110,000) was from Aldrich Chemie.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of preparing PDPB samples in PVA and the measurements of absorption spectra at differ ent temperatures were reported in [1]. PDPB was from Dr. D. Gloyna (Humboldt-Universität zu Berlin), poly (vinyl alcohol) (PVA, 100% hydrolyzed, molecular weight 106,000-110,000) was from Aldrich Chemie.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter cases, i.e. for l,6-diphenyl-l,3,5-hexatriene (DPH) and 1,8-diphenyl-l,3,5,7-octatriene (DPO) in PVA, an unusual behaviour of absorbance and quantum yield was ob served above the glass transition temperature (Tg = 358 K), which enabled the conclusion that above this temperature thermal cis-trans isomerization occurs in the ground state [1,3,5,6]. In addition, based on quantum yield and mean fluorescence lifetime decay measurements it was found that for the three polyenes fluorescence emission is due to trans-trans and cistrans conformers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of measuring the absorption and fluorescence spectra, and the quantum yields and emission anisotropies were described in [15][16][17]. Fluorescence decays were measured on a K 2 multifrequency cross-correlation phase and modulation fluorometer at the Biochemistry Department of the University of Ancona, Italy.…”
Section: Wavelength [Nm]mentioning
confidence: 99%
“…Chattopadhyay et al [14] obtained <*> F = 0.085 and r = 6.7 ns, = 0.088 and x = 1.1 ns and <P F = 0.091 and x = 6.8 ns in cyclohexane, benzene and methanol, respectively. Recently, unusual behaviour of the DPO absorbance and quantum yield was observed in polyvinyl alcohol) (PVA) films at temperatures above 358 K [15,16]. At such temperatures the absorbance and quantum yield strongly increase.…”
Section: Introductionmentioning
confidence: 99%